2023
DOI: 10.1891/jcpsy-d-20-00058
|View full text |Cite
|
Sign up to set email alerts
|

Does Using a Mindfulness App Reduce Anxiety and Worry? A Randomized-Controlled Trial

Abstract: Objectives:the availability of smartphone-based mindfulness training applications (apps) may circumvent many barriers to receiving in-person help, but little controlled research has been conducted on them. This study sought to evaluate the effectiveness of a widely used ­mindfulness training app, Headspace, at reducing anxiety and worry.Methods:this study used a randomized-controlled design to examine the app using a 3 (Time; baseline, 4 weeks, 8 weeks) × 2 (Access; immediate, delayed for 4 weeks) design. Part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Three studies found an effect favoring the intervention group, with small to large effect sizes 45 , 46 , 53 , and one of these had an active control group 53 . Two studies that found that neither group improved were underpowered 52 , 54 . Studies that found a between-group difference (versus none) had samples with a greater female composition.…”
Section: Resultsmentioning
confidence: 99%
“…Three studies found an effect favoring the intervention group, with small to large effect sizes 45 , 46 , 53 , and one of these had an active control group 53 . Two studies that found that neither group improved were underpowered 52 , 54 . Studies that found a between-group difference (versus none) had samples with a greater female composition.…”
Section: Resultsmentioning
confidence: 99%